Perceptions and experiences of police officers and social workers within South African Police Service when assisting women who survived sexual violence in Mamelodi, Pretoria - Bahula, Ikageng Maphale (University of the Witwatersrand, Johannesburg, 2023)
Many women are often reluctant to disclose cases of sexual violence to healthcare workers, police officers, family members etc. mainly due to the stigma attached. Few studies have been conducted to explore the experiences and perceptions of different role players within South African Police Officers (SAPS) when assisting women who survived sexual violence. Therefore, this study aimed to explore the perceptions and experiences of police officers and social workers within SAPS when assisting women who survived sexual violence. This study adopted a qualitative research approach, specifically a multiple case study design. The feminist poststructuralist theory was employed to guide the study. Three different interview guides were used as the research instrument. Individual face-to-face semi-structured interviews were used as the method of data collection. The sample size comprised twenty-five (25) different role players within SAPS in Mamelodi, Pretoria; five (5) client service centre police officers who work at both Mamelodi east and west police stations; ten (10) police officers who work in the special unit addressing sexual violence (FCS) at Mamelodi and ten (10) social workers who assist the survivors of sexual violence at both Mamelodi east and west police stations. The data gathered from the research were analysed using thematic analysis. The perceptions around sexual violence differs. This is influenced by the roles they play, how they have been exposed sexual violence and the school of thoughts. It is important that the service providers are oriented towards the concept and the practice on what sexual violence is. The service providers experience different challenges in different ways. Some challenges can be tackled at the individual level, while other challenges are societal, systematic and structural. Knowledge, attitude and practice of service providers require attention in terms of understanding the legal policies, the protocols and the practices in the sector.
A dissertation on a research study presented in fulfilling the requirements for the degree Master of Arts (Social Work) by research to the Department of Social Work, Faculty of Humanities, School of Human and Community Development University of the Witwatersrand, Johannesburg, 2023.
Keywords: South African Police Service; Social Work; Sexual violence; Women; Experiences; Perceptions; UCTD